Variation in Performance Strategies of a Hand Mental Rotation Task on Elderly - Nagashima, Izumi; Takeda, Kotaro; Shimoda, Nobuaki; Harada, Yusuke; Mochizuki, Hideki (Frontiers in Human Neuroscience, 2019)
A hand mental rotation task (HMRT) is a task wherein a person judges whether an image of a rotated hand is of the right or left hand. Two performance strategies are expected to come into play when performing these tasks: a visual imagery (VI) strategy, in which an image is mentally rotated, and a motor imagery (MI) strategy, in which the movement of a person’s own hand is simulated. Although elderly people generally take some time to perform these tasks, ability differs greatly between individuals. The present study hypothesizes that there is a relationship between differences in task performance strategy and performance ability, and it compares performance strategy among elderly people divided into groups with a short mental rotation time and a long mental rotation time. In response to images of the palm, both groups displayed a medial-lateral effect in which responses were faster for images where the third finger was rotated toward the midline of the body than images rotated in the opposite direction, and we inferred that an MI strategy was primarily employed. Meanwhile, in response to images of the back of the hand, a medial-lateral effect was also observed in the group with a long mental rotation time and not in the group with the shortest mental rotation time (VI strategy). These results suggest that different strategies for performing HMRT tasks are used by elderly people with a short mental rotation time and those with a long mental rotation time.